Fostering Environmental Ethics through Eco-Theology Based Recycling Creativity among Primary School Students - Melani Aftan; Suripto Suripto; Siti Nur Hidayatul Hasanah (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2026)
Environmental problems caused by plastic waste remain a serious challenge, including in primary education. The low level of students’ awareness of waste management highlights the need to strengthen environmental character from an early age. This community service activity aimed to strengthen students’ environmental ethics through eco-theology-based recycling creativity at SDN 1 Ngantru, Ngantru District, Tulungagung Regency. The activity employed an educational-participatory approach consisting of eco-theology and environmental ethics education, demonstrations, hands-on practice in transforming used plastic gallons into plant pots, reflection, and evaluation. The participants were 45 second- and third-grade students. The success of the activity was assessed qualitatively based on three main indicators: students’ understanding of eco-theology and the importance of environmental protection, students’ environmentally responsible behavior during the activity, and their ability to produce functional plant pots from used plastic gallons. Evaluation was conducted through observation of student participation and behavior, assessment of students’ responses to questions about the learning materials, and evaluation of their recycled products. The results showed that more than 90% of students actively participated throughout the activity, while all groups successfully produced plant pots of acceptable quality. Students also demonstrated the ability to explain the learning materials, maintain cleanliness, and develop practical skills in reusing plastic waste. Integrating eco-theological values with recycling activities provided students with a learning experience that connected environmental knowledge, character development, and practical skills. Therefore, an educational-participatory approach based on eco-theology has potential as an applicable environmental education model for strengthening environmental awareness and responsible environmental behavior among primary school students.